Analisis Yuridis Pelaksanaan E-Tilang Dalam Penanganan Pelanggaran Lalu Lintas - M. Rikki Ramadhan; Alpi Sahari; Surya Perdana (Mahesa Research Center, 2020)
Nowadays public service by the state apparatus has become a strategic issue because the level of quality of public service performance will determine the image of the state apparatus itself. The large number of complaints from the public as recipients of services to government agencies, illustrates how poor service quality has been in the past. Like public complaints that are often received due to slow service times and unclear service procedures and costs in resolving cases of traffic violations. On-line traffic violations are intended to overcome various problems related to the implementation of speeding tickets for traffic violations. The research method used in this thesis is analytical descriptive with normative legal research. Data collection techniques in this study use library research techniques as an instrument of document studies. In addition, interviews with informants are also carried out. Data analysis uses analysis qualitatively. The implementation of the synergy of online ticketing public services for the handling of traffic violations starting from the police to the court session stage has implemented the settlement of traffic violations through the sophistication of a computerized system that is connected to the entire BRI ATM network so that the public does not have to go to the prosecutor's office or the court. to solve the problem and without having to attend a court hearing by conducting an electronic payment system or e-commerce.